Targeting IFNα to tumor by anti-PD-L1 creates feedforward antitumor responses to overcome checkpoint blockade resistance. Issue 1 (December 2018) - Liang, Yong; Tang, Haidong; Guo, Jingya; Qiu, Xiangyan; Yang, Zecheng; Ren, Zhenhua; Sun, Zhichen; Bian, Yingjie; Xu, Lily; Xu, Hairong; Shen, Jiao; Han, Yanfei; et al.
Abstract Many patients remain unresponsive to intensive PD-1/PD-L1 blockade therapy despite the presence of tumor-infiltrating lymphocytes. We propose that impaired innate sensing might limit the complete activation of tumor-specific T cells after PD-1/PD-L1 blockade. Local delivery of type I interferons (IFNs) restores antigen presentation, but upregulates PD-L1, dampening subsequent T-cell activation. Therefore, we armed anti-PD-L1 antibody with IFNα (IFNα-anti-PD-L1) to create feedforward responses. Here, we find that a synergistic effect is achieved to overcome both type I IFN and checkpoint blockade therapy resistance with the least side effects in advanced tumors. Intriguingly, PD-L1 expressed in either tumor cells or tumor-associated host cells is sufficient for fusion protein targeting. IFNα-anti-PD-L1 activates IFNAR signaling in host cells, but not in tumor cells to initiate T-cell reactivation. Our data suggest that a next-generation PD-L1 antibody armed with IFNα improves tumor targeting and antigen presentation, while countering innate or T-cell-driven PD-L1 upregulation within tumor. Despite the presence of tumor-infiltrating lymphocytes, many patients do not respond to PD-L1/PD-1 blockade therapy. Here they show that PD-L1 antibody armed with interferon-α (IFNα) improves tumor targeting and antigen presentation while countering innate or T-cell-drive PD-L1 upregulation, and overcomes resistance to checkpoint blockade therapy.